Answer:
1.5 bananas to make each sundaes
Step-by-step explanation:
6 divided by 4
Answer: No, it is not a solution
Work Shown:
-2 ≤ k/3
-2 ≤ -9/3
-2 ≤ -3
The last inequality is false because -3 should be smaller than -2 (not the other way around). Use a number line to help see this.
Since the last inequality is false, the original inequality must also be false for that particular k value. Therefore, k = -9 is not a solution.
The answer is: [A]: " 20a − 5b − 9 " .
______________________________________
Explanation:
_______________________________________________
(12a <span>+ 7b) + (−6a − 9) + (14a − 12b) =
12a </span><span>+ 7b + 1(−6a − 9) + 1(14a − 12b) =
</span>
12a + 7b + (1*-6a) + (1*-9) + (1*14a) + (1* -12b) =
12a + 7b − 6a − 9 + 14a − 12b = ?
Combine the "like terms:
12a − 6a + 14a = 20a ;
7b − 12b = - 5b ;
and then we have "-9" ;
_____________________________________________________
So, write as: " 20a − 5b − 9 " ; which is: Answer choice: [A].
______________________________________________________
Answer:
step 2
Step-by-step explanation:
we have
---> given problem
step 1
Move the constant to the right side
the step 1 is correct
step 2
Complete the square
<u><em>The step 2 is not correct</em></u>
step 3
Rewrite as perfect squares
step 4
take square root both sides
step 5
Find the values of x
This work is faster rate than grading 36 assignments in 30 minutes because :
25 ÷ 20 = 1.25
1.25 hw assignment per minute
36 ÷ 30 = 1.2
1.2 hw assignments per minute